Possibilities of biodiversity conservation in agricultural fields - Csíder, Ibolya (Acta Agraria Debreceniensis, 2014)
The biodiversity loss is one of the biggest environmental problems in the world. The objective of this paper is to present some nature conservation practices on agricultural land. Farmlands play a significant role to preserve biodiversity because some highly protected species can only find their needs on agricultural land. The Biodiversity Strategy of the European Union (2010-2020) creates new directives to reduce biodiversity loss, preserve and improve diversity, especially on agricultural land. Furthermore the importance of this subject is that the share of farmland in Hungary is much higher (57%) than in the EU-27 on average (42%). The loss of agricultural land and the increase of land abandonment cause intensification of agricultural production leading to the loss of biodiversity.